Improving Academic Skills on Freshmen Student Performance in Mastering Learning Skills - Iyai, Deny Anjelus; Syaranamual, Siska; Yaku, Alexander (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to describe the capacity of students' learning skills, provide and develop problem-solving learning skills, prepare appropriate modules that are used by students, and encourage counseling and learning development units. The method used in this action research is a qualitative research design. The research technique was carried out by using a case study approach and observation. The results showed that the students' mathematical abilities ranged from 26-50 (57.14%). Only 14% (11.43% + 2.86%) of AgtSP students have capacities in basic mathematics. Learning skills, for example, reading and writing, had lower AgtSP values, namely 37.14% and 34.29%. AgtSP is still dominated by Papuan students (86%) and a small proportion of non-Papuan students (14%). Many students enrolled in AgtSP graduated from Social Sciences (38%), some graduated from Agricultural High School (33%), and a few graduated from natural sciences 21%) and a small number of students graduated from Non. Agricultural Senior High School, namely administration interest. Student GPA has increased in the number of students who have GPA scores. 23 components affect student learning skills at the university level as experienced by AgtSP. The conclusion is the low scores obtained by mathematics, reading, and writing students enrolled in the Faculty.